Such a pretty face - Lamb, Cathy (Kensington Books, 2010)
After losing 150 pounds from bariatric surgery, Stevie Barrett finds that life isn't so easy as a thinner person, as she contends with a jealous friend, bad romantic relationships, and a difficult family dynamic.